Assessment of convection‐permitting versions of the Unified Model over the Lake Victoria basin region. (28th February 2021) - Hanley, Kirsty E.; Pirret, Jennifer S. R.; Bain, Caroline L.; Hartley, Andrew J.; Lean, Humphrey W.; Webster, Stuart; Woodhams, Beth J.
Abstract: The Met Office runs an operational high‐resolution convection‐permitting model over Tropical Africa to support National Meteorological Services across the continent. This article evaluates the prediction of convective storms in two convection‐permitting versions of the Met Office Unified Model over the Lake Victoria basin region in East Africa. Two model configurations are compared for a case of severe convection: the first was tuned for tropical regions and the second was based on the operational UK model configuration. The tropical configuration compares better with satellite‐derived rainfall observations in terms of domain‐average rain‐rate and the distribution of rain‐rates is better, particularly for the more intense rain‐rates. However, both configurations generally produce too much rain, too many small storms, and a lack of light rain, which is compensated for by heavy rain in the cores of the storms. The tropical configuration was then assessed over two rainy seasons. In both seasons, the onset time of night‐time precipitation over Lake Victoria is delayed and the amount of precipitation is underestimated, which suggests the model may miss night‐time storms that occur over the lake. During the first 12–24 hr of the simulations, the precipitation field is still spinning up from the lower‐resolution global model fields used to initialise the convection‐permitting model. This leads to large overestimates in the domain‐average precipitation during this period and highlights the need to run convection‐permitting models for at least two days to reduce the impact of cold‐starting from a non‐convective‐permitting analysis. Despite the spin‐up issues, fractions skill score analysis shows that forecast skill decreases with increasing lead time. This implies that there is inherent skill in the early stages of the model forecast and underlines that short‐term forecast (0–48 hr) improvements in the model are likely to be achieved when using an improved analysis for initialisation. Abstract : This article evaluates the prediction of convective storms in convection‐permitting versions of the Met Office Unified Model over the Lake Victoria basin region in East Africa. The model generally produces too much rain, too many small storms, and a lack of light rain which is compensated for by heavy rain in the cores of the storms. Assessment over two rainy seasons highlights that the spin‐up of the model convection takes 18–24 hr, meaning that the day 2 forecast is often more reliable than day 1.